Filter‐based control of a buck converter for uncertain non‐linear loads. Issue 17 (1st February 2021) - Bhagwat, Bhagyashri A.; Alqatamin, Moath; Hawkins, Nicholas; McIntyre, Michael L.
Abstract : In this study, a filter‐based control scheme is proposed for dc–dc buck‐type converters. Primarily, this control scheme reduces costs by requiring only a single output voltage measurement, removing the need for potentially noisy current measurements. The proposed controller is compared with a Type III error amplifier, which is a linear controller commonly used for buck‐type converters. The performance of these controllers is compared when applied to linear and non‐linear loads. A Lyapunov stability analysis is utilised to demonstrate the system stability of the proposed control scheme. Experimental results demonstrate excellent voltage regulation and insensitivity to the load variations for the proposed controller as compared to Type III controller.